Mechanical and dissociation properties of methane hydrate-bearing sand in deep seabed - Hyodo, Masayuki; Yoneda, Jun; Yoshimoto, Norimasa; Nakata, Yukio (Soils and foundations, 2013)
A series of triaxial tests has been carried out on the mechanical properties and dissociation characteristics of sands containing methane hydrate using an innovative high pressure apparatus which has been developed to reproduce the in-situ conditions expected during proposed methane extraction methods. It was found that the strength of MH sand increased with MH saturation due to particle bonding. Dissociation by heating caused large axial strains for samples with an initial shear stress and total collapse for samples consolidated in the metastable zone. In the case of dissociation by de-pressurization, axial strains were generated by increasing effective stress until a stable equilibrium was reached. However, re-pressurization led to the collapse in the metastable zone.